Case Study On The Application Of The Brisk Walking Exercise Technique For Reducing Blood Pressure In Hypertensive Patients - Sinta Wijayanti; Marlina Diyan Safitri; Fitri Nuriya Santy; Shanty Chloranyta; Elok Faradisa (Sekolah Tinggi Ilmu Kesehatan Sumber Waras, 2025)
Hypertension is one of the chronic diseases with a very high prevalence worldwide, influenced by various factors such as environment, genetics, lifestyle, and the use of certain medications like birth control pills. Increased blood pressure in hypertensive patients has a significant impact on the risk of serious cardiovascular complications such as heart disease, heart failure, stroke, and kidney failure. Blood pressure control can be achieved thru self- management, which includes medication adherence, healthy lifestyle changes such as regular physical activity, and a low-sodium diet. One effective physical activity for lowering blood pressure in hypertensive patients is brisk walking. Based on this, this study aims to determine the effect of the brisk walking exercise technique on lowering blood pressure in hypertensive patients at RSD dr. A. Dadi Tjokrodipo Bandar Lampung. The method used by the researcher in this study is descriptive with a case study approach. The measuring instrument in this study used a sphygmomanometer, and the brisk walking exercise technique was applied according to the SOP. The research findings indicate a decrease in blood pressure among hypertensive patients after performing brisk walking exercise daily for eight days. The brisk walking exercise technique can lower blood pressure in hypertensive patients at RSD dr A. Dadi Tjokrodipo Bandar Lampung.